Análisis de los Procesos Contables de Bienes e Inventarios de la Universidad Técnica de Babahoyo - Villacrés Ortiz, Jonathan Euclides (2018)
The Technical University of Babahoyo with the number of RUC: 1260001110001 located Av. Universitaria Km 21/2 Av. Montalvo was created on October 5, 1971 under decree of the president of the republic Dr. José María Velasco Ibarra who signed decree 1580 where he says. Art 1.- Creation of the Technical University of Babahoyo with the respective Faculties of Education Sciences, Agricultural Engineering, and Veterinary Medicine in the city of Babahoyo in it. Art 2.- According to the decree that the University will receive its state budget from the year 1972. The current Rector is Dr. Rafael Falconi Montalván. The departments that are in charge of the accounting processes of goods and inventories, of the Technical University of Babahoyo are the Department of Control of Goods and Inventories and the Department of Financial Management are the ones that merge to generate the accounting, since each one It is responsible for specific functions that are necessary to generate the accounting process as established by the Ministry of Economy and Finance of Ecuador. "The accounting process in an organization is the set of steps that a company makes to know its economic situation for decision making." (Tamayo & Escobar, 2013, page 24) The problem of this project was born in 2016 when the management of the accounting process changed due to the control innovations that the Ministry of Economy and Finance implemented through a program for the Control of Goods and Inventories that directly affected the accounting process.